2018
DOI: 10.1111/jpc.13935
|View full text |Cite
|
Sign up to set email alerts
|

The use of overnight oximetry in neonates: A literature review

Abstract: There is much debate between neonatologists and paediatricians about appropriate oxygen saturation targets for babies with chronic neonatal lung disease (CNLD). Overnight oximetry is used to guide the fraction of inspired oxygen to use. We did this literature review to examine the current literature on the use of overnight oximetry in term infants, preterm infants and babies with CNLD (especially relevant to ex-preterm babies with CNLD going home on oxygen). We reviewed the literature from January 1990 to Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Oximeters and their analysis software are advancing in technology, but there are few detailed guidelines on how these recordings should be performed or interpreted . In New Zealand (NZ), there are guidelines from 2009 from Auckland's Starship Children's Hospital on performing and interpreting paediatric oximetry.…”
mentioning
confidence: 99%
“…Oximeters and their analysis software are advancing in technology, but there are few detailed guidelines on how these recordings should be performed or interpreted . In New Zealand (NZ), there are guidelines from 2009 from Auckland's Starship Children's Hospital on performing and interpreting paediatric oximetry.…”
mentioning
confidence: 99%
“…14,15 There is currently a paucity of literature describing recorded nocturnal oximetry at home in infants with BPD who clinically appear ready to wean from supplemental oxygen. 16,17 With the capability to detect subtle desaturation events that may not be readily apparent by clinical observation, we sought to gather more insight to high-risk patterns associated with both short-and long-term morbidity that may have been previously unrecognized. We performed a descriptive review of recorded nocturnal oximetry data collected in infants with BPD who were discharged home with supplemental oxygen to evaluate whether oximetry tests identified otherwise undetected hypoxemia in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Some centers have suggested that PSGs should be performed in all infants on HOT before discontinuing oxygen, where it is considered the gold standard for diagnosing sleep‐disordered breathing 8–10 . PSGs provide several respiratory parameters, but not all parameters may be relevant to determine whether oxygen can be discontinued.…”
Section: Introductionmentioning
confidence: 99%